2015
DOI: 10.1371/journal.pone.0138802
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent is Primate Second Molar Enamel Occlusal Morphology Shaped by the Enamel-Dentine Junction?

Abstract: The form of two hard tissues of the mammalian tooth, dentine and enamel, is the result of a combination of the phylogenetic inheritance of dental traits and the adaptive selection of these traits during evolution. Recent decades have been significant in unveiling developmental processes controlling tooth morphogenesis, dental variation and the origination of dental novelties. The enamel-dentine junction constitutes a precursor for the morphology of the outer enamel surface through growth of the enamel cap whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 49 publications
1
45
2
3
Order By: Relevance
“…A recent study [14] confirms that isolated silica phytoliths can produce striations on the enamel surface during mastication [20,21]. These results place the plant defences hypothesis [22][23][24][25][26] at the forefront of the debate as selective pressure towards dental innovations such as enamel thickening, tooth lengthening or hypsodonty [27][28][29]. Apart from food mechanical properties and bio-silica in plant tissues [30], soil and windblown mineral particles deposited on food found in arid habitats can also contribute to tooth wear [12,31].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…A recent study [14] confirms that isolated silica phytoliths can produce striations on the enamel surface during mastication [20,21]. These results place the plant defences hypothesis [22][23][24][25][26] at the forefront of the debate as selective pressure towards dental innovations such as enamel thickening, tooth lengthening or hypsodonty [27][28][29]. Apart from food mechanical properties and bio-silica in plant tissues [30], soil and windblown mineral particles deposited on food found in arid habitats can also contribute to tooth wear [12,31].…”
Section: Introductionmentioning
confidence: 71%
“…foods that are hard, tough and/or rich in silica phytoliths). Hence, food can be assumed to be one of the key factors promoting dental innovations such as molar hypsodonty in ruminants [6,27], molar lengthening in suids [29] or enamel thickening in hominids during the Neogene [28,44]. Among those, robust australopithecines have received a lot of attention over the last few years [13].…”
Section: Discussionmentioning
confidence: 99%
“…The third pattern was unique in that it was found only in Chiropotes, in which enamel deposition is fully responsible for the highly complicated OES. In addition to the occlusal patch count, the elevation, inclination, orientation, and curvature were used as quantitative criteria [29,30]. The comparative approach for the primate maxillary second molars confirmed that EDJ morphology was significantly correlated with OES morphology and that the disparity between them was attributable to enamel thickness.…”
Section: Shape Descriptorsmentioning
confidence: 93%
“…According to this estimate, a tooth with a small area of very high flat tips or a tooth with a large area of low flat polygons could have the same relief index. This variable also shows a strong negative correlation with RFI, but it has never been used for dietary inferences (Guy et al, ; Guy, Lazzari, Gilissen, & Thiery, ).…”
Section: Introductionmentioning
confidence: 99%
“…This also means that a tooth with a single high cusp and another one with a single deep valley could theoretically have the same height variation and, therefore, the same average slope and the same RFIs. Similarly, height variation is expected to be independent from the number of structures and may be the same between a tooth with a single tall cusp and another tooth with a large number of small structures such as cusplets, folds, wrinkles, and crenations (Bailey, Skinner, & Hublin, ; Butler, ; Guy et al, ).…”
Section: Introductionmentioning
confidence: 99%